Broad phylogeny and functionality of cellulosomal components in the bovine rumen microbiome. (28th October 2016) - Bensoussan, Lizi; Moraïs, Sarah; Dassa, Bareket; Friedman, Nir; Henrissat, Bernard; Lombard, Vincent; Bayer, Edward A.; Mizrahi, Itzhak
Summary: The cellulosome is an extracellular multi‐enzyme complex that is considered one of the most efficient plant cell wall‐degrading strategies devised by nature. Its unique modular architecture, achieved by high affinity and specific interaction between protein modules (cohesins and dockerins) enables formation of various enzyme combinations. Extensive research has been dedicated to the mechanistic nature of the cellulosome complex. Nevertheless, little is known regarding its distribution and abundance among microbes in natural plant fibre‐rich environments. Here, we explored these questions in bovine rumen microbial communities, specialized in efficient degradation of lignocellulosic plant material. We bioinformatically screened for cellulosomal modules in this complex environment using a previously published ultra‐deep fibre‐adherent rumen metagenome. Intriguingly, a large portion of the functions of the dockerin‐containing proteins were related to alternative biological processes, and not necessarily to the classic fibre degradation function. Our analysis was experimentally validated by characterizing specific interactions between selected cohesins and dockerins and revealed that cellulosome is a more generalized strategy used by diverse bacteria, some of which were not previously associated with cellulosome production. Remarkably, our results provide additional proof of similarity among rumen microbial communities worldwide. This study suggests a broader and widespread role for the cellulosomal machinery in nature.